Travelogue elements in Krleža’s letters - Kajba-Šimanić, Klara (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
Bela, dear child is a collection of one hundred selected letters exchanged between Bela and Krleža between 1918 and 1981. By studying Krleža’s letters, one can see the interweaving of different genres. The subject of analysis will be ways of recording space and travelogue elements in epistolary form. Krleža sends letters from different European cities and conveys his impressions with short dothematization and forms interesting socio-political images of the cities where he stays. Krleža’s imagological constructions are scattered fragmentarily through numerous letters in which the travel subject discovers the worlds of famous cities through the eyes of an artist. His stays abroad are closely related to his creativity and to the construction of his identity as a European writer.